A review on nursing reserve team in hospital emergency management - Liu, Min; Shetty, Ganesh Beloor (Edelweiss Applied Science and Technology, 2025)
The Nursing Reserve Team plays a pivotal role in managing hospital emergencies, providing critical support during crises. This paper reviews recent research on the effectiveness of nursing reserve teams, highlighting their contributions to emergency management and public health preparedness. Historically rooted in disaster response, nursing’s role has evolved to encompass a wide range of responsibilities, including emergency care, psychological support, and management during crises. Despite their importance, significant gaps in emergency preparedness training for nurses have been identified, particularly in light of past public health emergencies like SARS, H1N1, and COVID-19. This paper underscores the need for comprehensive training programs that enhance nurses’ knowledge and skills, ensuring they are equipped to respond effectively to emergencies. It advocates for the empowerment of nursing reserve teams within healthcare facilities to bolster overall emergency response capabilities. By articulating the roles and responsibilities of nursing professionals in disaster preparedness, this study emphasizes the crucial link between nursing education, practice, and the ability to safeguard public health during emergencies. Investing in continuous training, institutional support, and formal recognition of nursing reserve teams is essential to build a robust, responsive healthcare system capable of withstanding future crises.